A Case of Malignant Biliary Obstruction with Severe Obesity Successfully Treated by Endoscopic Ultrasonography-Guided Biliary Drainage - Takashi Obana; Shuuji Yamasaki (Case Reports in Medicine)
Here, we present a case of malignant biliary tract obstruction with severe obesity, which was successfully treated by endoscopic ultrasonography-guided biliary drainage (EUS-BD). A female patient in her sixties who had been undergoing chemotherapy for unresectable pancreatic head cancer was admitted to our institution for obstructive jaundice. She had diabetes mellitus, and her body mass index was 35.1 kg/m2. Initially, endoscopic retrograde cholangiopancreatography (ERCP) was performed, but bile duct cannulation was unsuccessful. Percutaneous transhepatic biliary drainage (PTBD) from the left hepatic biliary tree also failed. Although a second PTBD attempt from the right hepatic lobe was accomplished, biliary tract bleeding followed, and the catheter was dislodged. Consequently, EUS-BD (choledochoduodenostomy), followed by direct metallic stent placement, was performed as a third drainage method. Her postprocedural course was uneventful. Following discharge, she spent the rest of her life at home without recurrent jaundice or readmission. In cases of severe obesity, we consider EUS-BD, rather than PTBD, as the second drainage method of choice for distal malignant biliary obstruction when ERCP fails.